Visual mate preference evolution during butterfly speciation is linked to neural processing genes - Matteo Rossi (Nature Portfolio, 2020)
The genetic mechanisms underlying mate choice decisions can inform our understanding of speciation. A study on Heliconius butterflies identifies 5 candidate genes that would allow sympatric species to evolve distinct preferences without altering their visual perception of the wider environment.